The cross-disciplinary perspectives of management : challenges and opportunities - Weber, Yaakov; Vrontis, Demetris; Tsoukatos, Evangelos; Shams, S. M. Riad (Cross-disciplinary management perspectives, 2019)
Whilst existing studies on research management focus on single disciplinary perspectives in isolation, this new collection integrates a range of theories and business models from multiple fields to offer insights and examples of cross-disciplinary management perspectives. As the workplace environment encounters increased disruption and discontinuity, both researchers and practitioners are facing new and unique managerial challenges. Using alternative research methods from two or more scientific and practitioner disciplines, including Sociology, Politics, Psychology and Technology, the chapters suggest numerous solutions to a wide range of challenges. Some of the challenges explored include: Mind-Genomics and data-driven personalized health plans; the high failure rate of mergers and acquisitions; business ecosystems and start-ups; and, international businesses confronting globalization. Generating innovative research findings, as well as practical managerial solutions, The Cross-Disciplinary Perspectives of Management: Challenges and Opportunities aids both scholars and managers to find solutions to existing managerial challenges across a range of industries and disciplines.